An illustrated catalogue of the New Zealand marsh beetles (Coleoptera: Scirtidae) - Kiałka, Agata; Ruta, Rafał (Zootaxa, 2017)
In this study we summarise the knowledge of the history and current state of research on the New Zealand Scirtidae to provide a base for further research on the family. Data on Tord Nyholm’s research and collections are presented, based on a study of the archives and collection of Swedish Museum of Natural History. The main part of the paper is a catalogue of all described species of Scirtidae known to occur in New Zealand. A total of 11 genera and 126 species of Scirtidae is recorded for New Zealand, with 82% genera and 100% of species endemic to the New Zealand region. A reference to the original description, type locality, type depository and the known distribution within New Zealand is included for each species. Primary type specimens are illustrated for most species. Type species are designated in the present paper for Cyphanus Sharp, 1878 (type species: Cyphanus debilis Sharp, 1878), Mesocyphon Sharp, 1878 (type species: Mesocyphon marmoratus Sharp, 1878), and Veronatus Sharp, 1878 (type species: Anobium tricostellum White, 1846) as they were not fixed in the original descriptions or in subsequent works. Brounicyphon Pic, 1947 is considered a junior subjective synonym of Veronatus. Cyphon huttoni Sharp, 1878 is transferred to the genus Contacyphon Gozis, 1886.